Design and Development of a Web-Based Quranic Verse Submission Application at Al-Uswah Islamic Boarding School Pekanbaru - Megawati Megawati; Harisman Efendi; Febi Nur Salisah; Fitriani Muttakin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The process of Quran recitation submission at Al-Uswah Islamic Boarding School in Pekanbaru involves interaction between students and teachers for submitting and evaluating Quran memorization. This research aims to develop a Quran Recitation Submission WebApp based on ReactJS for the frontend and Firebase as the backend. The application was developed using the Rapid Application Development method and tested through Blackbox Testing and User Acceptance Testing (UAT). The development results show that all features function well, with positive feedback from users. The main features of the application include hafiz ranking, online recitation submission, and the ability for teachers to provide feedback to students.